Combined approach to analyze and classify families of classical spin liquids - Davier, N. (2023)
Classical spin liquids have been a very active subject of research in the last few years. A very rich variety of cases have been shown to exist, including short-range and algebraic spin liquids displaying dipolar correlations at zero temperature. In this article, we investigate different families of classical spins liquids by combining analytical techniques and Monte Carlo simulations. Our study relies on the Luttinger-Tisza Approximation (LTA), which is associated with the constraint vector function in momentum space, whose general properties allow for a classification of different spin liquids. We show that the general properties of the LTA provide a framework for identifying and accurately characterizing the different types of spin liquids in different geometries. We apply our approach to three different families of spin liquids defined on the checkerboard and kagome lattices, which exhibit a remarkable range of situations, including various cases of algebraic and short-range spin liquids. Additionally, we analyze the effective Gauss law emerging from different kinds of spin liquids and identify states that exhibit additional degeneracy lines. The presence of spin liquid phases and pinch point singularities are confirmed by Monte Carlo simulations validating our approach. Our study opens up new avenues of research in the study of spin liquids, exploring algebraic spin liquids with higher-rank gauge fields and as critical points dividing different types of classical spin liquids.